2019
DOI: 10.21037/atm.2019.08.79
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive circular RNA profiling identifies CircFAM120A as a new biomarker of hypoxic lung adenocarcinoma

Abstract: Background: Hypoxia is crucial in the initiation and progression of tumor metastasis. Circular RNAs (CircRNAs) comprise a novel group of non-coding, RNase R resistant and regulatory RNAs which are generated by 'back-splicing' processes. However, the characterization and function of circRNAs in hypoxic cancer cells remain unknown.Methods: High throughput RNA-seq assay was performed in lung adenocarcinoma cells (A549) under either normoxic or hypoxic conditions. Bioinformatic analysis of differentially expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…We observed that circ_0008193 was significantly downregulated in LUAD tumor tissues and cell lines, as well as in hypoxia-treated A549 and H1975 cells (with HIF1A upregulation). These data agreed with a previous study [ 29 ]. In this study, we further examined the biologic role of circ_0008193 in LUAD cells.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…We observed that circ_0008193 was significantly downregulated in LUAD tumor tissues and cell lines, as well as in hypoxia-treated A549 and H1975 cells (with HIF1A upregulation). These data agreed with a previous study [ 29 ]. In this study, we further examined the biologic role of circ_0008193 in LUAD cells.…”
Section: Discussionsupporting
confidence: 94%
“…Dozens of circRNAs have also been declared to be significantly abundantly altered upon hypoxia in cervical, breast, and lung cancer cells in vitro [ 28 ]. Moreover, the circRNA expression profile was comprehensively compared in A549 cells under normoxia and hypoxia [ 29 ]. Since hypoxia is crucial to the initiation and progression of tumor metastasis, several circRNAs have been demonstrated to participate in LUAD cell migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a novel hotspot of the ncRNA field, hypoxia-responsive circRNAs (HRCs) have been shown to be of great importance. However, unlike miRNAs and lncRNAs, the mechanisms of HIF-1α-mediated HRC expression are not fully understood [28]. Similarly, several studies uncovered that HIF-1α can directly regulate cir-cRNAs at the transcriptional level through HREs, but more mechanisms have not been reported [29].…”
Section: Regulation Of Ncrnas By Hif-1αmentioning
confidence: 99%
“…In addition, the expression of circFAM120A was significantly downregulated in both hypoxic lung adenocarcinoma cells and cancer tissue from patients with lymph node metastasis, implying its potential to be a new biomarker of lung adenocarcinoma hypoxia [28]. Moreover, circRNAs lack a 5' cap and 3' ends, endowing them with more stable properties than parent linear RNAs [191].…”
Section: Perspectives On Hif-1α and Ncrnas In Clinical Practicementioning
confidence: 99%